Effect of Periodic Bottom Plate Heating on Large Scale Flow in Turbulent Rayleigh-Bénard Convection - Margarita Kuqali; Simone Babuin; Joseph Niemela (Journal of Applied Fluid Mechanics, 2015)
We report analysis of temperature fluctuations measured inside a Rayleigh-Bénard convection cell of aspect ratio unity with steady and time-varying heating of the bottom boundary. The working fluid is cryogenic helium gas at Rayleigh number Ra = 1013, for which a large scale coherent flow (mean wind) exists. We observe the wind to occasionally vanish under both steady and time-varying heating conditions. However, with applied periodic modulation of the lower boundary temperature at the frequency of the wind, we can observe destruction of the periodic temperature variation at the cell mid-plane, due to relative changes in phase between the mean wind and the propagating temperature wave. The wind speed is not observed to change with modulation, demonstrating that it is set by mean properties of the system. Finally we propose that the frequency of the mean wind – and hence the large scale Reynolds number – could be better resolved by finding resonance with applied forcing.